Brief Report: Proteasomal Indoleamine 2, 3-Dioxygenase Degradation Reduces the Immunosuppressive Potential of Clinical Grade-Mesenchymal Stromal Cells Undergoing Replicative Senescence. (23rd February 2017) - Loisel, Séverine; Dulong, Joëlle; Ménard, Cédric; Renoud, Marie-Laure; Meziere, Nadine; Isabelle, Bezier; Latour, Maëlle; Bescher, Nadège; Pedeux, Rémy; Bertheuil, Nicolas; Flecher, Erwan; Sensebé, Luc; et al.
Abstract : Owing to their immunosuppressive properties, mesenchymal stromal cells (MSCs) obtained from bone marrow (BM-MSCs) or adipose tissue (ASCs) are considered a promising tool for cell therapy. However, important issues should be considered to ensure the reproducible production of efficient and safe clinical-grade MSCs. In particular, high expansion rate, associated with progressive senescence, was recently proposed as one of the parameters that could alter MSC functionality. In this study, we directly address the consequences of replicative senescence on BM-MSC and ASC immunomodulatory properties. We demonstrate that MSCs produced according to GMP procedures inhibit less efficiently T-cell, but not Natural Killer (NK)- and B-cell, proliferation after reaching senescence. Senescence-related loss-of-function is associated with a decreased indoleamine 2, 3-dioxygenase (IDO) activity in response to inflammatory stimuli. In particular, although STAT-1-dependent IDO expression is transcriptionally induced at a similar level in senescent and nonsenescent MSCs, IDO protein is specifically degraded by the proteasome in senescent ASCs and BM-MSCs, a process that could be reversed by the MG132 proteasome inhibitor. These data encourage the use of appropriate quality controls focusing on immunosuppressive mechanisms before translating clinical-grade MSCs in the clinic.